Alterations of the outer retina in non‐arteritic anterior ischaemic optic neuropathy detected using spectral‐domain optical coherence tomography. (9th March 2017) - Ackermann, Philipp; Brachert, Maike; Albrecht, Philipp; Ringelstein, Marius; Finis, David; Geerling, Gerd; Aktas, Orhan; Guthoff, Rainer
Abstract: Background: A characteristic disease pattern may be reflected by retinal layer thickness changes in non‐arteritic anterior ischaemic optic neuropathy measured using spectraldomain optical coherence tomography. Retinal layer segmentation is enabled by advanced software. In this study, retinal layer thicknesses in acute and chronic non‐arteritic anterior ischaemic optic neuropathy were compared. Design: A single‐centre cross‐sectional analysis was used. Participants: A total of 27 patients (20 age‐matched healthy eyes) were included: 14 with acute (<7 days) and 13 patients with chronic non‐arteritic anterior ischaemic optic neuropathy. Methods: Macular volume and 12° peripapillary ring optical coherence tomography scans were used. Main Outcome Measures: The peripapillary thicknesses of the following layers were determined by manual segmentation: retinal nerve fibres, ganglion cells + inner plexiform layer, inner nuclear layer + outer plexiform layer, outer nuclear layer + inner segments of the photoreceptors and outer segments of the photoreceptors to Bruch's membrane. Macular retinal layer thicknesses were automatically determined in volume cubes centred on the fovea. Results: Peripapillary retinal swelling in acute nonarteritic anterior ischaemic optic neuropathy was attributable to retinal nerve fibre layer, ganglion cell layer/inner plexiform layer and outer nuclear layer/segments of the photoreceptors thickening. In chronic cases, peripapillary retinal nerve fibre layer, macular ganglion cell layer and inner plexiform layer thinning were observed. Conclusions: In acute non‐arteritic anterior ischaemic optic neuropathy, the inner and outer peripapillary retinal layers are affected by thickness changes. In chronic cases, atrophy of the ganglion cells and their axons and dendrites is evident by inner retinal layer thinning.